Synthesis, spectral characterization and cytotoxic activity of 3D-transition metal complexes with O-vanillin benzoylhydrazone ligand - Husna Sarfina, Bt Husain (Universiti Malaysia Sarawak, UNIMAS, 2012)
Six new Mn(II), Fe(II), Co(II), Ni(II), Cu(II) and Zn(II) complexes (2-7) of o-vanillin benzoylhydrazone ligand (1) have been synthesized and characterized. The ligand (1) and its 3dmetal complexes (2-7) were characterized by elemental analysis, molar conductivity, UVVisible, FT-IR and 1H NMR spectroscopic studies. The spectroscopic data of the complexes (2- 7) suggested that the ligand (1) is acted as a dinegative tridentate chelating system and is coordinated to central metal(II) atom through phenoxide-O, atomethine-N and carboxylate-O atoms. Four coordinated molecular structure has been proposed for the synthesized 3d-transition metal complexes. The ligand (1) and its metal complexes (2-7) have also been tested for their cytotoxicity and found to be less active against Artemia salina.